Visible light driven photo-reduction of Cu2+ to Cu2O to Cu in water for photocatalytic hydrogen production. Issue 10 (5th February 2020) - Cao, Shuang; Wang, Chuan-Jun; Wang, Guo-Qiang; Chen, Yong; Lv, Xiao-Jun; Fu, Wen-Fu
Abstract : A visible-light-driven system for photoreduction of Cu(ii ) to Cu2 O to Cu(0) and identification of Cu(0) as the active catalyst for hydrogen production. Abstract : Metal nanoparticles are synthesized via various methods and have found many applications in areas such as sensing, electronics and catalysis. Light induced formation of noble metal nanoparticles, especially platinum, in solution or loaded on semiconductor surfaces, is an established practice in photocatalysis. Nevertheless, preparation of catalytically-active non-precious metal nanoparticles via photo-reduction still have room to be further explored. Here, we report a visible light driven system that can coordinate photo-reduction of CuSO4 to selectively prepare Cu2 O or Cu nanoparticles, while at the same time, mediating efficient hydrogen production with in situ generating Cu catalyst without further need to add any components. The Cu2 O and Cu nanoparticles in situ generated are crystalline in nature and can perform as pre-catalyst (Cu2 O) or catalyst (Cu) to catalyze hydrogen production when reincorporated into the same photo-reduction system with organic photosensitizers. Our work offers an exploratory pathway to prepare target metal nanoparticles while provides some insight into harnessing solar energy for multi-functional purposes.